The Impact of Endoscopic Stapler Selection on Bleeding at the Vascular Stump in Pulmonary Artery Transection - Tsunezuka Y (Dove Medical Press, 2020)
Yoshio Tsunezuka, Nobuhiro Tanaka, Hideki Fujimori Department of General Thoracic Surgery, Ishikawa Prefectural Central Hospital, Kanazawa, JapanCorrespondence: Yoshio TsunezukaDepartment of General Thoracic Surgery, Ishikawa Prefectural Central Hospital, Kuratsukihigashi 2-1, Kanazawa 920-8530, JapanTel +81-76-237-8211Fax +81-76-238-2337Email tsuney@nifty.comObjective: To assess bleeding following transection of the pulmonary artery with powered and manual endoscopic staplers.Methods: Cases of video-assisted and open-chest thoracic surgical procedures for non-small cell lung cancer at Ishikawa Prefectural Central Hospital were reviewed between 2012 and 2018. Three stapler groups were assessed: Group 1 – Ethicon ECHELON FLEXTM Powered Vascular Stapler (PVS), Group 2 – Medtronic Endo-GIATM iDriveTM powered stapler, Group 3 – Ethicon and Medtronic manual staplers.Results: Of 239 patients, 82 cases (34.3%) were Group 1, 94 cases (39.3%) were Group 2 and 63 cases (26.4%) were Group 3. Mean age was 68.3 years (range 36– 88 years), and most patients received video-assisted right upper lobectomy (82.8%). Bleeding occurred in 24 cases: 17 (70.8%) in Group 2 and 7 (29.2%) cases in Group 3. No bleeding occurred in Group 1. The loaded ECHELON FLEXTM PVS and Endo-GIATM iDriveTM with gray cartridge combinations had the greatest and smallest closed anvil jaw gaps (> 0.63 μm and < 0.15 μm, respectively); Endo-GIATM iDriveTM gray cartridge combinations resulted in ruptures of inner and middle membranes of the pulmonary artery. No ruptures were observed using the ECHELON FLEXTM PVS.Conclusion: An excessively narrow gap between cartridge and anvil may damage the blood vessel wall and lead to bleeding following transection. This study provides preliminary evidence that the use of the ECHELON FLEXTM PVS and tan cartridges for pulmonary artery stapling may help to prevent tissue damage and intraoperative bleeding.Keywords: surgery, stapler, pulmonary artery, bleeding